Historical Background of Inclusive Education Development in the Nordic Countries - Andriichuk , Natalia (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The article analyzes and interprets the comprehensive presentation of the development of inclusive education in some Nordic countries, namely Sweden, Norway and Iceland. The article states that the special education is still an alternative form of education for children with special needs who cannot attend secondary schools in the majority of the countries. Thus, the relation between inclusive and special education allows the author to draw some parallels between these two types of study to trace the transition from one to another. The author concludes that the history of inclusive education formation in Sweden, Norway and Iceland has much in common, but the Icelandic education system has characteristics which distinguish it from the two others